THE EFFECT OF THE PEER MENTORING PROGRAM ON NURSING STUDENTS’ PROBLEM-SOLVING AND SELF-EFFICACY LEVELS: A UNIVERSITY EXAMPLE - Necmiye Çömlekçi; Ebru Cirban Ekrem; Emine Güneş Şan; Hilal Uysal (Sabuncuoglu Serefeddin Health Sciences, 2026)
Peer mentoring is a process in which the mentor student contributes to the personal, academic, and professional development of the mentee student by sharing their knowledge, skills, thoughts, and experiences. The primary goal of a peer mentoring program is the development of the mentee student. However, in this process, the mentor student fulfills the roles of educator, guide, counselor, and supporter, and this process also contributes to the development of the mentor student. In this study, it was aimed to determine the effect of a peer mentoring program implemented at a university on the problem-solving and self-efficacy levels of mentee and mentor students. The study was conducted using a quasi-experimental, multi-time-point, control-group design. The research data were collected between December 2023 and June 2024. The study sample consisted of a total of 26 students, including 13 mentees and 13 mentors who participated in the peer mentoring program, while the control group consisted of a total of 30 students, including 14 first-year students with similar characteristics to the mentee students and 16 third-year students with similar characteristics to the mentor students. A personal information form, the General Self-Efficacy Scale, and the Problem-Solving Inventory were used to collect the research data. Sociodemographic characteristics were similar in both groups (p>0.05). In comparisons between the mentor and mentor control groups, no significant differences were found in the General Self-Efficacy Scale, the total scores and subscale scores of the Problem-Solving Inventory, either within groups or between groups (p>0.05). In the mentee group, however, a statistically significant difference was found in the personal control subscale of the Problem-Solving Inventory compared to the mentee control group (p=0.001). Similarly, a significant difference was found in within-group time comparisons in the mentee control group (p=0.02). No significant differences were found in within-group or between-group comparisons over time for the mentee and mentee control groups. In conclusion, the peer mentoring program provided a significant improvement in the personal control subscale of the Problem-Solving Inventory in the mentee group. It is recommended that the study be replicated with larger sample groups and research designs with a higher level of evidence.